2019
DOI: 10.25083/rbl/24.6/1027.1033
|View full text |Cite
|
Sign up to set email alerts
|

Organic acids and sugars profile of some grape cultivars affected by grapevine yellows symptoms

Abstract: Grapevine yellows are a group of infectious diseases, which are usually associated with phytoplasma pathogens, affecting quality of grapes and survival of grapevine. The objective of this work was to evaluate sugars, total phenols and organic acids concentrations in the grapes of four wine cultivars (Fetească Neagră, Pinot Noir, Traminer rose, Chardonnay) healthy and affected by specific symptoms to phytoplasmoses. Berry samples were collected from the Miniș-Măderat (Arad County) and Odobești (Vrancea County) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Malic acid concentrations were found between 5.10 g/100 g FW (Clone 6) and 6.23 g/100 g FW (Clone 5) (Table 7). Previous studies have also indicated that tartaric acid was the main and dominant organic acid in grape juices followed by malic acid, and both organic acids accounted for 55-60% and 30-39% of the total organic acids in grape, respectively [2,68,69,73]. In Brazil, Couelho et al [74] found that tartaric acid was the main acid present in wines and juices representing over 50% of the total acids quantified.…”
Section: Organic Acid Contentmentioning
confidence: 98%
See 3 more Smart Citations
“…Malic acid concentrations were found between 5.10 g/100 g FW (Clone 6) and 6.23 g/100 g FW (Clone 5) (Table 7). Previous studies have also indicated that tartaric acid was the main and dominant organic acid in grape juices followed by malic acid, and both organic acids accounted for 55-60% and 30-39% of the total organic acids in grape, respectively [2,68,69,73]. In Brazil, Couelho et al [74] found that tartaric acid was the main acid present in wines and juices representing over 50% of the total acids quantified.…”
Section: Organic Acid Contentmentioning
confidence: 98%
“…Previous studies have indicated that grape berries are rich in glucose and fructose, and the values of these major sugars, were found to be closer to each other. Studies have also indicated that glucose and fructose content and their ratio greatly changed according to cultivar, growing conditions, etc., in grapes [2,68,69], and both dominant sugars account for 96.00-98.00 of the total sugar content in grape berries. Petrisor and Chirecanu [68] also reported that sucrose content was very low (even nondetectable) in all grape cultivars and they found the ratio of glucose/fructose in grape berries varied in range from 1.0 to 1.06.…”
Section: Sugar Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies indicated that fructose and glucose content and ratio greatly changed according to grape cultivar, growing conditions, cultural treatments, etc. [25,26]. Zhang et al [27] showed that among the five varieties of table grapes grown in China, fructose content is slightly higher than glucose and both sugars, accounting for 96.00-98.00% of the total sugar contents in grape berries.…”
Section: Sugar Contentmentioning
confidence: 99%